Dynamic Sliding Mode Evolution PWM Controller for a Novel High-Gain Interleaved DC-DC Converter in PV System - Taizhou Bei; Ping Wang; Liu Yang; Zhe Zhou (Journal of Applied Mathematics)
Considering the disadvantages of the traditional high-gain DC-DC converter such as big size, high voltage stress of switches, and large input current ripple, a novel high-gain interleaved boost converter with coupled-inductor and switched-capacitor was proposed correspondingly and the operation principle together with the steady-state analysis of this converter was also described. Besides, a new control approach-dynamic sliding mode evolution PWM controller (DSME PWM) for the novel topological converter based on both dynamic evolution and sliding mode control was also presented. From the simulation results and experimental validation the proposed converter can fulfill high-gain boost, low ripple of both the input current and the output voltage. Furthermore, MPPT technique can be also achieved in a short time by simulation. The efficiency and stability of the converter proposed in this paper can be improved.